Combination of Raman tweezers and quantitative differential interference contrast microscopy for measurement of dynamics and heterogeneity during the germination of individual bacterial spores - Zhang, Pengfei; Kong, Lingbo; Wang, Guiwen; Setlow, Peter; Li, Yong-Qing (My University, 2010)
Raman tweezers and quantitative differential interference contrast (DIC) microscopy are combined to monitor the dynamic germination of individual bacterial spores of Bacillus species, as well as the heterogeneity in this process. The DIC bias phase is set properly such that the brightness of DIC images of individual spores is proportional to the dipicolinic acid (DPA) level of the spores, and an algorithm is developed to retrieve the phase image of an individual spore from its DIC image. We find that during germination, the rapid drop in both the intensity of the original DIC image and the intensity of the reconstructed phase image precisely corresponds to the release of all DPA from that spore. The summed pixel intensity of the DIC image of individual spores adhered on a microscope coverslip is not sensitive to the drift of the slide in both horizontal and vertical directions, which facilitates observation of the germination of thousands of individual spores for long periods of time. A motorized stage and synchronized image acquisition system is further developed to effectively expand the field of view of the DIC imaging. This quantitative DIC technique is used to track the germination of hundreds or thousands of individual spores simultaneously.
Keywords: Raman microscopy Bacillus DIC